Prevalence of Malaria and COVID-19 Infection in Akure North Local Government Area of Ondo State, Nigeria - Iyabo Adepeju Simon-Oke; Oluwaseun Bunmi Awosolu; Olatunji Odeyemi (Journal of Parasitology Research)
Introduction. The prevalence of malaria and coronavirus disease (COVID-19) is highly devastating and has led to a serious public health challenge worldwide. In order to ensure proper control and elimination, the State Ministry of Health (MoH) Ondo State, Nigeria conducted medical examinations in Iju/Itaogbolu, Igoba, and Ogbese Health centers to identify and confirm cases of COVID-19 and malaria infection. This study provides the outcome of the epidemiological investigation of the prevalence of COVID-19 and malaria in Akure North Local Government Area of Ondo State, Nigeria. Method. The study was a hospital-based secondary data analysis comprising of 11,389 and 682 individuals who visited various health centers in Akure North Local Government Area (LGA) for medical examinations on malaria and COVID-19, respectively. The COVID-19 cases were investigated using the fluid sample collected with a nasal swab or a throat swab, or spit of saliva into a tube and confirmed by real-time polymerase chain reaction (RT-PCR). The Plasmodium falciparum histidine-rich protein 2 (PfHRP2) RDT was employed to detect the P.falciparum antigen among participants’ blood samples. Results. The total prevalence of malaria and COVID-19 were 67.6% and 12.4%, respectively. Meanwhile, the month of September recorded the highest malaria prevalence of 81.8% while the month of April recorded the least malaria prevalence of 56.4%. Similarly, the highest case of COVID-19 (18.8%) was recorded in the month of November while the least case (2.4%) was recorded in the month of April (p<0.05). The age range of 12-59 months had the highest malaria prevalence of 74.9% while 0-24 days age range recorded the least prevalence of 15.2% (p>0.05). Apparently, the children were more infected with malaria parasites while adults were more infected with COVID-19. Conclusion. Conclusively, malaria and COVID-19 infections were prevalent in the study area. Thus, the people should be enlightened on the deadly risk of malaria and COVID-19 through the health workers, social media, and the community leaders to ensure compliance with appropriate preventive measures.